THE ROLE OF THE MEDIA IN COVERING ETHNIC ISSUES: A CENTRAL ASIA AND THE CAUCASUS CASE STUDY - ESENOV, Murad (CENTRAL ASIA AND THE CAUCASUS, 2012)
Ethnic conflicts are one of the most problematical and sensitive issues known to the world today. Since World War II, for example, more than 100 armed conflicts have broken out in different parts of the world, most of which are ethnic in nature.1 These conflicts pose a threat to state security and territorial integrity and, in their extreme form, are accompanied by violence, bloodshed, mass violations of human rights, huge numbers of refugees, significant material losses, and so on. So, it stands to reason that the media pay a great deal of attention to covering different aspects of ethnic issues. By offering the broad public information on this subject, the media not only inform people, but also generate mass ideas and moods with respect to ethnic relations. This makes the way the media presents and interprets the ethnic life of different peoples extremely important. For example, V.K. Malkova expressed the following thought on this count: “The ideas, views, and attitudes of people toward peaceful coexistence and ethnic conflicts largely, although not entirely, depend on how tolerantly or intolerantly information is presented in the press.”2 So, the information about ethnic issues conveyed to the mass consciousness through the media can either be conducive to tolerance or evoke hostility. It is a well-known fact that ethnic information conveyed in a tolerant light promotes the emergence of positive images of the members of a particular ethnic group in the public consciousness and arouses a keen interest in and respectful attitude toward their way of life, customs, traditions, achievements, and ethnic history. This information is aimed at creating postures of ethnic consent in society, consolidating a polyethnic population, and so on. Intolerant ethnic information, on the other hand, has the dangerous tendency to disunite people. It generates racial and ethnic differences in society, exaggerating ideas about the ethnic incompatibility of different groups of the population, instilling thoughts about the threat posed by members of a particular ethnicity, and giving rise to hostile feelings toward “outsiders,” etc.